Determining the relationship between upper and lower body strength/mass ratios on double pole performance in cross-country skiing on flat and inclined terrain using absolute, standard ratio, and allometric scaling - Sederquist, R. (Adams State University, 2022)
The double pole (DP) technique, which engages the upper and lower body, is the most often used technique in classic ski competitions. Races are often won on uphills, where the primary mechanical impediment is gravity. Therefore, research analyzing the relationship between both upper body strength/body mass and lower body strength/body mass and DP performance on flat and uphill terrain, using standard ratio, absolute and allometric ratio, is a worthy enterprise. Nine (9) athletes, 7 men and 2 women completed two rollerski double pole time trials, one on flat terrain (1200 m) and one on inclined terrain (1000 m), as well as three upper body strength tests and a test for lower body strength. Relationships between upper and lower body strength using absolute, standard ratio, and allometric scaling were analyzed using a Pearson's product-moment correlation coefficient. The key findings were: 1) There is a strong correlation between upper and lower body strength/mass relationships and double pole performance at incline and on the flat terrain using all three scalings. Using allometric scalings, the correlation between seated double pole and double pole performance was statistically significant on flat (r = -0.96) and inclined (r = -0.90) terrain. Absolute scalings of the seated double pole were also statistically significant on flat (r = -0.88) and inclined (r = -0.94) terrain. While the seated double pole is the most sport specific exercise to the double pole, the bench press also showed strong relationships with time trial performance on flat (absolute, r = -0.92; standard ratio, r = -0.81; allometric, r = -0.86) and incline (r = -0.93; standard ratio, r = -0.87; allometric, r = -0.89). Regarding lower body strength, all three scalings of leg press strength showed statistically significant (P < 0.05) or highly significant (P < 0.01) correlations with incline and flat double pole performance. 2) The strongest correlation between lower body strength and double pole performance at inclines (r = -0.90) and on the flat (r = -0.93) came using absolute scalings of lower body strength. Allometric scaling on the flat (r = -0.88) and inclined (r = -0.89) terrains was also statistically significant (P < 0.05), as was standard ratio on flat (r = -0.75) and inclined terrain (r = -0.72). 3) Allometric and standard ratio scalings of upper and lower body strength/body mass tended to have a stronger correlation with double pole performance on inclined terrain compared to flat terrain, suggesting that perhaps, when the effect of gravity increases, so too does the influence of strength in relation to body mass. Using standard ratio scaling, the correlation coefficient of the seated double to performance on flat terrain was r = -0.48, while on inclined terrain, the correlation coefficient was r = -0.68. There was a similar difference between flat (r = -0.59) and incline (r = -0.75) with bench pull and leg press (flat, r = -0.72; incline, r = -0.75). Using allometric scaling of the bench pull, correlations to flat (r = -0.79) performance was also lower than performance at an incline (-0.89). This was also true in the bench press (flat, r = -0.86; incline, r = -0.89). This confirms prior research supporting the importance of upper and lower body sport-specific strength development for cross-country ski performance, particularly with the double pole subtechnique. Practical applications exist primarily for long-distance skiing, where double pole is used exclusively, but recommendations for traditional classic and skate skiing, regarding upper and lower body strength development with respect to body mass, are also discussed.